Urgensi Pelaksanaan SMK3 di Sektor Pendidikan: Studi Kasus di Perguruan Tinggi - Auliya Syifa; Dewi Purnamawati (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2025)
This study aims to describe and analyze the urgency of implementing the Occupational Health and Safety Management System (OHSMS) in higher education, focusing on its implementation at University. The research employs a descriptive qualitative approach using semi-structured interviews, field observations, and literature review to gather data on the challenges and successes in the implementation of OHSMS. The results show that although the OHSMS has been effectively implemented through the preparation of Standard Operating Procedures (SOPs) and the provision of safety facilities, the main challenges are the lack of awareness among the academic community and insufficient ongoing training. Some measures, such as the installation of safety signs and the provision of APAR, have been successfully implemented, but there is still a need for improved socialization and training to ensure optimal OHSMS implementation. This study recommends enhancing practical training and more intensive socialization to improve understanding of safety procedures among all members of the academic community.